1996
DOI: 10.1007/bf01769874
|View full text |Cite
|
Sign up to set email alerts
|

Invasive mold infections in cancer patients: 5 years' experience withAspergillus, Mucor, Fusarium andAcremonium infections

Abstract: Twenty systemic mold infections due to hyphic fungi (molds) arising within the last 5 years in a 60-bed cancer department are analyzed. The most frequent risk factors were plants in ward (75%), prior therapy with broad spectrum antibiotics (70%), catheter insertion (70%), acute leukemia (65%) and neutropenia (60%). Before death, a definitive diagnosis was made in 40%, and a presumptive diagnosis in 60% of patients: post mortem the presumptive antemortem diagnosis was confirmed in all cases (100% of patients). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…In one autopsy-proven study of invasive mold infections in cancer patients, 10% of the cases were caused by Acremonium spp. (14). The present case of peritonitis highlights the clinical importance of A. kiliense in human infections.…”
Section: Case Reportmentioning
confidence: 60%
See 1 more Smart Citation
“…In one autopsy-proven study of invasive mold infections in cancer patients, 10% of the cases were caused by Acremonium spp. (14). The present case of peritonitis highlights the clinical importance of A. kiliense in human infections.…”
Section: Case Reportmentioning
confidence: 60%
“…The last 2 decades have witnessed a steady increase in the spectrum of hyaline fungi incriminated as opportunistic pathogens in immunocompromised patients (5,14,28). Many soil saprobes and plant pathogens with no obvious pathogenic potential have now emerged as etiologic agents under a variety of clinical conditions, thus posing new diagnostic and therapeutic challenges (38).…”
Section: Case Reportmentioning
confidence: 99%
“…It has already been reported that aspergillosis (55%) is the most common invasive fungal disease, followed by mucormycosis (zygomycosis) (15%), fusariosis (15%), and acremoniosis (10%) (25). The pathogenic fungi responsible for these disease were not considered previously to be important human pathogens but are widely present in soil, plants, and elsewhere in the environment.…”
Section: Structural Characterization Of Oligosaccharides Of Ngls-mentioning
confidence: 99%
“…Invasive fungal infections are a major medical problem, particularly among immunocompromised hosts such as patients with hematological malignancies and those who have undergone stem cell or solid organ transplantation (3,8,20,22,23,33). Some fungal species, including Fusarium spp., rarely cause disease but are considered emerging pathogens (8,23).…”
mentioning
confidence: 99%